MITIGATING THE RISK OF EMBEZZLEMENT OF COMPANY CAPITAL BY AN EMPLOYEE : IMPLEMENTING FRAUD PREVENTION MEASURES TO PROTECT THE PROCUREMENT PROCESS FOR BUYING LAYING CHICKEN FEED AT DAZ FARM - Arkananta Wirananda (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This research investigates the financial and operational challenges faced by DAZ Farm, a small-scale laying hen farm in West Java, Indonesia, with a particular focus on fraud risk and its impact on business sustainability. The research identifies fraudulent activities committed by an employee, highlighting weaknesses in inventory management, financial oversight, and employee accountability. Using a descriptive qualitative methodology, the study applies the Fraud Triangle, Risk Matrix, and Business Process Flowchart as analytical tools to uncover systemic vulnerabilities and prioritize solutions. Data collection involves in-depth interviews with key stakeholders and analysis of operational and financial records. The findings reveal that key risk factors include a lack of internal monitoring systems, manual record-keeping, and insufficient employee ethics training. High-risk issues such as dual roles for employees and inadequate segregation of duties create opportunities for fraud. Recommendations include implementing automated inventory and financial tracking systems, enhancing employee training, and establishing whistleblowing mechanisms. This study provides actionable insights to mitigate fraud risk, ensuring the operational and financial integrity of small-scale agricultural businesses.